Coagulopathy and haemorrhagic progression in traumatic brain injury: advances in mechanisms, diagnosis, and management. Issue 8 (August 2017) - Maegele, Marc; Schöchl, Herbert; Menovsky, Tomas; Maréchal, Hugues; Marklund, Niklas; Buki, Andras; Stanworth, Simon
Summary: Normal haemostasis depends on an intricate balance between mechanisms of bleeding and mechanisms of thrombosis, and this balance can be altered after traumatic brain injury (TBI). Impaired haemostasis could exacerbate the primary insult with risk of initiation or aggravation of bleeding; anticoagulant use at the time of injury can also contribute to bleeding risk after TBI. Many patients with TBI have abnormalities on conventional coagulation tests at admission to the emergency department, and the presence of coagulopathy is associated with increased morbidity and mortality. Further blood testing often reveals a range of changes affecting platelet numbers and function, procoagulant or anticoagulant factors, fibrinolysis, and interactions between the coagulation system and the vascular endothelium, brain tissue, inflammatory mechanisms, and blood flow dynamics. However, the degree to which these coagulation abnormalities affect TBI outcomes and whether they are modifiable risk factors are not known. Although the main challenge for management is to address the risk of hypocoagulopathy with prolonged bleeding and progression of haemorrhagic lesions, the risk of hypercoagulopathy with an increased prothrombotic tendency also warrants consideration.